Acute Splenic Sequestration Crisis in a 70-Year-Old Patient With Hemoglobin SC Disease. (16th March 2016) - Squiers, John J.; Edwards, Anthony G.; Parra, Alberto; Hofmann, Sandra L.
A 70-year-old African American female with a past medical history significant for chronic bilateral shoulder pain and reported sickle cell trait presented with acute-onset bilateral thoracolumbar pain radiating to her left arm. Two days after admission, Hematology was consulted for severely worsening microcytic anemia and thrombocytopenia. Examination of the patient's peripheral blood smear from admission revealed no cell sickling, spherocytes, or schistocytes. Some targeting was noted. A Coombs test was negative. The patient was eventually transferred to the medical intensive care unit in respiratory distress. Hemoglobin electrophoresis confirmed a diagnosis of hemoglobin SC disease. A diagnosis of acute splenic sequestration crisis complicated by acute chest syndrome was crystallized, and red blood cell exchange transfusion was performed. Further research is necessary to fully elucidate the pathophysiology behind acute splenic sequestration crisis, and the role of splenectomy to treat hemoglobin SC disease patients should be better defined.